2021
DOI: 10.1002/anie.202113334
|View full text |Cite
|
Sign up to set email alerts
|

A Conjugated Figure‐of‐Eight Oligoparaphenylene Nanohoop with Adaptive Cavities Derived from Cyclooctatetrathiophene Core

Abstract: Af ully conjugated figure-of-eight nanohoop is presented with facile synthesis.T he moleculesl emniscular skeleton features the combination of two strained oligoparaphenylene loops and af lexible cyclooctatetrathiophenec ore.Its rigid yet guest-adaptive cavities enable the formation of the peanut-like 1:2h ost-guest complexes with C 60 or C 70 ,w hich have been confirmed by X-ray crystallography and characterizedi ns olution. Further computational studies suggest notable geometric variations and non-covalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 119 publications
2
43
0
Order By: Relevance
“…Note that the single crystal of the complex was easier to achieve than the free-standing 6a, suggesting that C60 serves as a template for the crystal growth. 34 As shown in Figure 3a, a 1:1 host-guest complex formed with the C60 sited in the center of the nanohoop. The intermolecular distances of the host and the guest were in the range of 3.4-3.7 Å, indicating a dominant vdW interaction.…”
Section: Host-guest Complexation With C60mentioning
confidence: 96%
“…Note that the single crystal of the complex was easier to achieve than the free-standing 6a, suggesting that C60 serves as a template for the crystal growth. 34 As shown in Figure 3a, a 1:1 host-guest complex formed with the C60 sited in the center of the nanohoop. The intermolecular distances of the host and the guest were in the range of 3.4-3.7 Å, indicating a dominant vdW interaction.…”
Section: Host-guest Complexation With C60mentioning
confidence: 96%
“… 46 Same type of interactions are key in the synthesis of [10]cycloparaphenylene-fullerene [2]rotaxanes 47 and in the recently synthesized figure-of-eight nanohoop that forms peanut-like 1:2 host–guest complexes with C 60 or C 70 . 48 …”
Section: Introductionmentioning
confidence: 99%
“…46 Same type of interactions are key in the synthesis of [10]cycloparaphenylene-fullerene [2]rotaxanes 47 and in the recently synthesized figure-of-eight nanohoop that forms peanut-like 1:2 host−guest complexes with C 60 or C 70 . 48 Very recently, Ribas et al 49 reported the synthesis of a threeshell, matryoshka-like complex in which C 60 inside a [10]CPP is in turn encapsulated inside a self-assembled nanocapsule. Bingel cyclopropanation to this matryoshka-like complex leads to the selective formation of a particular fullerene bisadduct.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the development of host‐guest systems involving fullerenes has attracted much attention for chemical sensor, 1,2 supramolecular and electric materials, 3,4 nanoscale mechanics 5,6 and separation of specific fullerenes 7 . Carbon nanorings (CNRs) 8–14 and ligand–metal ring are two most popular hosts for fullerenes 15,16 . It is known that the selective and efficient encapsulation for the fullerene guests is an essential property in design of stable host‐guest supramolecular systems.…”
Section: Introductionmentioning
confidence: 99%